Rupture of endometriotic ovarian cyst causes acute hemoperitoneum in twin pregnancy - Reif, Philipp; Schöll, Wolfgang; Klaritsch, Philipp; Lang, Uwe (Fertility and sterility, 2011)
To present a case of an acute hemoperitoneum caused by a ruptured ovarian cyst in a late twin pregnancy. Case report study. Department of Obstetrics and Gynecology, Medical University of Graz, Austria. A woman with a history of surgery for endometriosis and currently pregnant with dichorionic twins after IVF presented with acute abdominal pain. Serial ultrasound assessment revealed a massive hemoperitoneum that was caused by a ruptured endometriotic ovarian cyst. Emergency laparotomy was performed. Hemostasis. Laparotomy led to operative hemostasis and preterm cesarean section of healthy twins at 27 weeks of gestation. Endometriosis occurs in about 10% of women of reproductive age and carries an infertility rate of up to 50%. Severe endometriosis used to be a rare event in patients with spontaneously conceived pregnancies. However, during the last decade, the increased use of assisted reproductive technologies has led to higher fertility rates in patients with endometriosis and to a higher incidence of multiple gestations. Therefore, the number of pregnant women with endometriosis and associated complications may rise.